The role of medical chemistry in the synthesis of selective anticancer compounds for breast cancer with a computational and experimental approach - Saeful Amin; Nikeu Rahayu; Hana Nurhanifah; Anggi Zulvana; Syamsiati Dwi; Ardina Malika (Universitas Pahlawan Tuanku Tambusai, 2025)
Breast cancer is a cancer with high prevalence in women and requires more selective therapy and minimal side effects. Medicinal chemistry plays an important role in the development of anticancer compounds through a chemical synthesis approach, in silico modeling, and in vitro validation. The aim of this study is to comprehensively review the role of medicinal chemistry in the synthesis and development of selective anticancer compounds in breast cancer, with an emphasis on computational (in silico) approaches and experimental validation as two inseparable aspects of the modern drug discovery and development process. This study examined twenty articles related to natural and synthetic compounds tested for cancer targets such as HER-2, CDK4, and DAPK1. Compounds such as luteolin and benzimidazole derivatives show high affinity and cytotoxic activity in MCF-7 cells. The results show that the integration of computational and experimental approaches supports the development of breast cancer therapy that is more effective and safe.